Social Innovation Program Sustainability Analysis: Implementation and Results at the Super-Man Program Sumanding, Jepara - Wahyu Mahaputra; Riyan Prasetyo; Ahmad Kharis (Prospect Publishing, 2023)
This research analyzes the social innovation contained in the Super-Man Program which focuses on the sustainability of Edu-Eco Farming by the Taruna Tani Group in Sumanding Village, Jepara Regency. The aim of this research is to understand and explore the implementation of social innovation in the form of the Super-Man Program which aims to increase the sustainability of Edu-Eco Farming and its impact on the community in Sumanding Village. This research uses a qualitative approach with a case study method, involving data collection through observation, interviews and document analysis. The research results show that the Super-Man Program has succeeded in implementing social innovation in the development of Edu-Eco Farming in Sumanding Village. This innovation includes the use of local resources, the use of minimal input from outside, a combination of food crops, basic sustainable biological principles, sustainable ecology, and the use of appropriate technology. The success of the Super-Man Program is reflected in several things, including a portrait of the element of novelty of the Super-MAN Sumanding program which can produce new products, new production processes and new markets. Apart from that, it also creates local livestock markets, agricultural products, and environmentally friendly plantations.